Conversational strategies in children’s talk - Daraškienė, Inga; Hilbig, Inga (Taikomoji kalbotyra, 2019)
The aim of this article is to investigate linguistic and non-linguistic conversational strategies and their realisations, employed by five year olds in peer interactions. 5 hours and 49 minutes of recorded children’s talk were used for the analysis. The data were processed using Transana software, and qualitative conversation analysis was applied. The analysis reveals that children are more inclined to use conversational strategies that motivate cooperation and solidarity rather than competition or dominance in a conversation. Dialogues mostly involve comments and questions, followed by repetitions of both speaker’s own or the interlocutor’s words. Jokes are also used to maintain or restart conversations and to support or restore friendly relationships. Strategies that break the symmetry of conversation are rarely applied. The conversation is sometimes interrupted when opposing the partner or establishing a leader role. Silence as a conversation strategy also serves to communicate disagreement with partner’s statements. Overall, the research subjects appear to be pragmatically competent interlocutors, adhering to the main principles of adult conversation: able to wait for their turn in conversation, choose and change its topic appropriately, involve the interlocutor in it or regain his/her attention if needed, and solve communicational break-downs and conflicts. However, the results presented are to be confirmed by further studies and through more various child-to-child conversations.
Keywords: child discourse; child-to-child conversations; conversational strategies; pragmatic competence; linguistic pragmatics